Analisis Pengembangan Material Komposit Berbasis Serat Alam untuk Aplikasi Rekayasa Struktur Modern - Anwar, Muhammad Khairul; Adillah, Ilham Basith; Ramadhan, Muhammad Dzikri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to ignite the potential of using ramie fiber (Boehmeria nivea) as an alternative composite reinforcement material in supporting the Green Manufacturing trend. The main problem in using natural fiber is the low interfacial bond due to the natural wax layer on the fiber surface. Through a theoretical analysis and benchmarking approach, this study reviews the effectiveness of alkali treatment (NaOH) and the modern manufacturing method Vacuum Assisted Resin Infusion (VARI). The analysis results show that surface engineering through alkalization is theoretically able to increase the microscopic roughness of the fiber which is crucial for mechanical interlocking with the matrix. The benchmarking results show that the ramie composite has a density that is 40% lighter than glass fiber (E-glass), with a competitive specific strength. It is concluded that the integration of ramie fiber and the VARI method offers a lightweight, quality-stable, and sustainable material solution for implementation in future industrial structures.